Diabetes - Metcalf, Tom; Metcalf, Gina (Detroit : Thomson Gale, 2008)
Presents essays on diabetes, discussing such topics as its causes, the two types of diabetes, diagnosis of the disease, and different treatment methods, and contains profiles of three individuals and how they cope with diabetes.
Presents essays on diabetes, discussing such topics as its causes, the two types of diabetes, diagnosis of the disease, and different treatment methods, and contains profiles of three individuals and how they cope with diabetes.
Includes bibliographical references (p. 127-129) and index.
Keywords: Diseases; Diabetes mellitus